The R&D and innovation activity of agribusiness enterprises in Hajdú-Bihar County - Németh, Szabolcs (Acta Agraria Debreceniensis, 2013)
Economic changes have significantly accelarated in the 21th century. In this turbulent market environment enterprises are forced to adapt continously as they must be flexible in order to meet changing market needs. To achieve flexibility companies require innovation. The economic relevance of innovations is significant in every market sector and agriculture is no exception. Re-dynamizing agricultural innovations is a possibility for the outburst of the Hungarian agriculture. Agricultural enterprises have to face competitors as well and they should give priority to efficiency, sustainability and competitiveness in order to preserve their position in BOTH global and domestic markets. This study examines the innovation potential of the agricultural enterprises in the North Great Plain region based on own databases and case studies.